2002
DOI: 10.1182/blood.v99.3.1060
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of parasite proteins to altered mechanical properties of malaria-infected red blood cells

Abstract: Red blood cells (RBCs) parasitized byPlasmodium falciparum are rigid and poorly deformable and show abnormal circulatory behavior. During parasite development, knob-associated histidinerich protein (KAHRP) and P falciparum erythrocyte membrane protein 3 (PfEMP3) are exported from the parasite and interact with the RBC membrane skeleton. Using micropipette aspiration, the membrane shear elastic modulus of RBCs infected with transgenic parasites (with kahrp or pfemp3 genes deleted) was measured to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
233
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(246 citation statements)
references
References 29 publications
8
233
0
Order By: Relevance
“…In agreement with previous reports, we found that asexual trophozoite-infected RBCs are highly undeformable (Nash et al, 1989). This loss of deformability is probably due to a combination of membrane rigidification and the presence of the large rigid intracellular parasite (Glenister et al, 2002;Nash et al, 1989). We found that stage III gametocytes have similar deformability properties to trophozoiteinfected RBCs; however, upon transition to stage IV the gametocytes show a significant increase in the elongation index measured under flow conditions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous reports, we found that asexual trophozoite-infected RBCs are highly undeformable (Nash et al, 1989). This loss of deformability is probably due to a combination of membrane rigidification and the presence of the large rigid intracellular parasite (Glenister et al, 2002;Nash et al, 1989). We found that stage III gametocytes have similar deformability properties to trophozoiteinfected RBCs; however, upon transition to stage IV the gametocytes show a significant increase in the elongation index measured under flow conditions.…”
Section: Discussionsupporting
confidence: 92%
“…P. falciparum is also unusual among human malaria parasites in that late stage asexual parasites drastically remodel the RBC through the export and insertion of parasite-derived proteins into and under the host RBC membrane . These modifications lead to a significant increase in cellular rigidity, which would make mature parasite-infected RBCs vulnerable to recognition and clearance within the spleen (Glenister et al, 2002;Safeukui et al, 2008). The parasite avoids these clearance mechanisms by cytoadhereing within the microvasculature of the host.…”
Section: Discussionmentioning
confidence: 99%
“…Major changes that occur in the infected erythrocyte include the formation of small protrusions on the surface of the cell (knobs), alterations in ion channel behaviour (Decherf et al 2004;Staines et al 2007), the formation of novel channels for nutrient import (Saliba et al 1998;Desai et al 2000;Staines et al 2004), membrane rigidity and cell deformability (Glenister et al 2002) and altered behaviour of infected erythrocytes in the microcirculation (DiezSilva et al 2012). These modifications occur as a result of the export of various effector proteins in the infected erythrocyte.…”
Section: H O S T -C E L L M O D I F I C At I O N a N D P R O T E I N mentioning
confidence: 99%
“…The study of RBCs at the cellular level has shown that the infection of RBCs can impair their rheological properties [11][12][13][14][15][16][17][18][19][20].…”
Section: Correlation With Diseasesmentioning
confidence: 99%